SMS messages – context for traditional and modern proverbs - Liisa Granbom-Herranen (Suomalainen Tiedeakatemia, 2022)
The article focuses on SMS messages as short letters in a Finnish daily newspaper, Salon Seudun Sanomat. A proverb is often included in the SMS message. The analysis is based on Charles Briggs’s (1988) research on a proverb’s performances. Proverbs in a spoken language are in many ways similar to proverbs in the colloquial written form; presentational features are the same. The research is also based on Lev Vygotski’s (1967) claim that a language is linked to a thought, and on Gottlob Frege’s (2000) principle of context. Thirdly, an utterance should follow Paul Grice’s (1975) cooperative principle of quantity, quality, relation, and manner. In what follows the meaning of the proverbs will be analyzed twofold; on the one hand we will analyze the meaning given by the writer, and on the other hand a basic meaning. Proverbs get new forms and flexible. Modern proverbs occur and the traditional ones are transformed. Proverbs are a part of a contemporary Finnish communication and everyday language use, although the context of use has changed over a period of one century.
Folkloristics in the digital age